Acute Symptomatic Sinus Bradycardia in High-Dose Methylprednisolone Therapy in a Woman With Inflammatory Myelitis: A Case Report and Review of the Literature. Issue 12 (February 2019) - Sodero, Alessandro; Squitieri, Martina; Mazzeo, Salvatore; Pasca, Matteo; Matà, Sabrina; Pieri, Francesco; Bessi, Valentina; Sorbi, Sandro
High dose corticosteroid therapy is widely used as attack therapy of inflammatory central nervous system disorders and can induce several adverse reactions. Bradycardia is an infrequent event after corticosteroids administration and is often asymptomatic. We report a case of a woman admitted to the neurological department of our hospital for paraesthesias of the lower limbs. She received adiagnosis of inflammatory myelitis and high dose corticosteroid therapy was prescribed. During the therapy she complained of chest tightness, dyspnoea, weakness and malaise. An electrocardiogram revealed sinus bradycardia. A significant increase in body weight, probably due to plasma volume expansion, was detected. Bradycardia and high blood pressure spontaneously resolved in few days. We provide a collection and a statistical analysis of literature data about steroid induced bradycardia. We found that higher total doses are associated with lower pulse rate and symptomatic bradycardia. Bradycardia is more frequent in older patients and those with underlying cardiac disease or with autonomic disturbance. However clinicians must be aware about the occurrence of symptomatic bradycardia in all patients who undergo high dose corticosteroid therapy, not only in those at risk, to early detect and treat this potentially dangerous condition.